2008
DOI: 10.1242/jeb.011882
|View full text |Cite
|
Sign up to set email alerts
|

Differential actions of diuretic factors on the Malpighian tubules ofRhodnius prolixus

Abstract: +]. Upper tubules responded to ZooneDH with a characteristic triphasic change in the transepithelial potential (TEP), reminiscent of the response to 5-hydroxytryptamine (5HT). RhoprDH 31 produced a small (~9·mV) lumen-positive shift in TEP of the upper tubule but had no effect on the rate of fluid secretion or ion composition of the secreted fluid. In contrast to 5HT, both peptides failed to activate KCl reabsorption by the lower tubule. Leucokinin I had no effect on the ion composition of fluid secreted by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Interestingly, however, Donini and colleagues (Donini et al, 2008) have suggested that the lower portion of the Malpighian tubules, where the reabsorption of K + occurs, is stimulated only by 5HT, not by Zoone DH. Studies are currently underway to look at the activity of the native peptide on the lower tubule.…”
Section: Activity Of Rhopr Dh On Native Tissuesmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, however, Donini and colleagues (Donini et al, 2008) have suggested that the lower portion of the Malpighian tubules, where the reabsorption of K + occurs, is stimulated only by 5HT, not by Zoone DH. Studies are currently underway to look at the activity of the native peptide on the lower tubule.…”
Section: Activity Of Rhopr Dh On Native Tissuesmentioning
confidence: 98%
“…In R. prolixus, studies comparing the activity of Zoone DH and 5HT on ion transport and transepithelial potential across the upper segments of Malpighian tubules (Donini et al, 2008), coupled with secretion and second messenger studies (Te Brugge et al, 1999;Te Brugge et al, 2002), suggest that CRF-like peptides and 5HT activate the same second messenger pathways and ion-transport mechanisms in the upper tubule cells. Interestingly, however, Donini and colleagues (Donini et al, 2008) have suggested that the lower portion of the Malpighian tubules, where the reabsorption of K + occurs, is stimulated only by 5HT, not by Zoone DH.…”
Section: Activity Of Rhopr Dh On Native Tissuesmentioning
confidence: 99%
“…CT-like DH is therefore likely to be released into the circulation along with serotonin shortly after the onset of feeding. A CT-like DH (Rhopr-DH 31 ) has been identified in Rhodnius (Te Brugge et al, 2008), but it has little effect on secretion by the upper tubule (Te Brugge et al, 2005) and has no effect on K + uptake from the lower tubule (Donini et al, 2008) Changes in diuretic hormone concentration have no effect on fluid secretion, which is already maximal, but will decrease (a) or increase (b) fluid absorption so as to restore haemolymph volume until the two rates are equal (arrow). Redrawn from Maddrell (Maddrell, 1980 …”
Section: Candidates For the Peptide Diuretic Hormone Of Rhodniusmentioning
confidence: 99%
“…In cross-species assays, kinins have no effect on secretion by the upper segment of Rhodnius tubules, and this has been confirmed with HPLC fractions from the MTGM that contain kinin-like immunoreactive material . Kinins also have no effect on K + uptake from the lower tubule (Donini et al, 2008) and fluid absorption from the crop (V. A. Te Brugge and I. Orchard, personal communication).…”
Section: Candidates For the Peptide Diuretic Hormone Of Rhodniusmentioning
confidence: 99%
“…The fact that many different hormones affect fluid secretion by Malpighian tubules had been known for some time [see paper by Coast in this issue (Coast, 2009)] (Donini et al, 2008). There is evidence for the Malpighian tubules of Manduca sexta that at least eight different sorts of compounds can significantly affect the rates of their fluid secretion (Skaer et al, 2002).…”
Section: Other General Problems With Insect Hormonesmentioning
confidence: 99%